A filosofia nos parâmetros curriculares nacionais para o ensino médio e as contribuições do pensamento complexo - Horvath, Wilson Agnaldo (2012)
This research proposes some reflection on the knowledge of Philosophy presented by the Parâmetros Curriculares Nacionais for High School considering the concepts of Ethycs and Civilization Policy, studied by Edgar Morin. The text is composed of four chapters; the first one brings the main subjects presented by the Parâmetros; the second presents the epistemological, social, ecological and political problems of our time; the third one explains how the complex thought establishes the dialogical relation between Ethics and Civilization Policy; and the fourth analyses the Parâmetros by presenting their advances and limits and proposes some complements that, as we realize, will help the teaching of Philosophy in answering to our present problems. We come to these results in our research: the Parâmetros were produced considering a social democratic ideology that distinguishes the citizen s participating actions in a political process, the control of the production means and the income distribution. There is a national perspective, but there isn t a global political worry, except the actions that directly interfere on the Brazilian economy and consequently on the population life. Their industrial growth view doesn t consider the effects against Nature. On the other hand, the contributions the complex thought brings to the document relate to the environment, to the feeling of belonging to Mother Land, what represents an alert towards the difficulty of foreseeing knowledge through the usage of technology.